Gray matter microglial activation in relapsing vs progressive MS: A [F-18]PBR06-PET study. Issue 5 (September 2019) - Singhal, Tarun; O'Connor, Kelsey; Dubey, Shipra; Pan, Hong; Chu, Renxin; Hurwitz, Shelley; Cicero, Steven; Tauhid, Shahamat; Silbersweig, David; Stern, Emily; Kijewski, Marie; DiCarli, Marcelo; et al.
Abstract : Objective: To determine the value of [F-18]PBR06-PET for assessment of microglial activation in the cerebral gray matter in patients with MS. Methods: Twelve patients with MS (7 relapsing-remitting and 5 secondary progressive [SP]) and 5 healthy controls (HCs) had standardized uptake value (SUV) PET maps coregistered to 3T MRI and segmented into cortical and subcortical gray matter regions. SUV ratios (SUVRs) were global brain normalized. Voxel-by-voxel analysis was performed using statistical parametric mapping (SPM). Normalized brain parenchymal volumes (BPVs) were determined from MRI using SIENAX. Results: Cortical SUVRs were higher in the hippocampus, amygdala, midcingulate, posterior cingulate, and rolandic operculum and lower in the medial-superior frontal gyrus and cuneus in the MS vs HC group (all p < 0.05). Subcortical gray matter SUVR was higher in SPMS vs RRMS (+10.8%, p = 0.002) and HC (+11.3%, p = 0.055) groups. In the MS group, subcortical gray matter SUVR correlated with the Expanded Disability Status Scale (EDSS) score (r = 0.75, p = 0.005) and timed 25-foot walk (T25FW) (r = 0.70, p = 0.01). Thalamic SUVRs increased with increasing EDSS scores (r = 0.83, p = 0.0008) and T25FW (r = 0.65, p = 0.02) and with decreasing BPV (r = −0.63, p = 0.03). Putaminal SUVRs increased with increasing EDSS scores (0.71, p = 0.009) and with decreasing BPV (r = −0.67, p = 0.01). On SPM analysis, peak correlations of thalamic voxels with BPV were seen in the pulvinar and with the EDSS score and T25FW in the dorsomedial thalamic nuclei. Conclusions: This study suggests that [F-18]PBR06-PET detects widespread abnormal microglial activation in the cerebral gray matter in MS. Increased translocator protein binding in subcortical gray matter regions is associated with brain atrophy and may link to progressive MS.